SEVERE HUNGRY BONE SYNDROME, COULD WE HAVE PROGNOSTICATED IT BETTER? A CASE SERIES - Mokhtar, Muzhaffar; MA, Masliza Hanuni; WA, Siti Sanaa; Mohamad, Hussain; Muda, Nor Hisham (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Hungry bone syndrome (HBS) is characterized by serum calcium less than 2.1 mmol/L and/or prolonged hypocalcaemia more than four days following parathyroidectomy or thyroidectomy. Here, we report two cases of HBS following parathyroidectomy for primary hyperparathyroidism (PHPT). CASE 1 A 17-year-old female was diagnosed with PHPT when she presented with bilateral femoral neck and humeral fractures. Her serum calcium was 3.69 (2.2-2.65 mmol/L), serum phosphate 0.92 (0.81- 1.45 mmol/L), and serum intact parathyroid hormone (iPTH) 1187.2 (14.9-56.9 pg/ ml). There was deficient 25-hydroxy vitamin D at 18.9 (<25 nmol/L), ALP was elevated at 1413 (47-162 U/L) and renal function was normal. Ultrasound (US) of the parathyroid showed a lobulated hypoechoic lesion at the posterior right thyroid, measuring 1.6 x 2.3 x 3.3 cm. Preoperatively she received IV bisphosphonates and subcutaneous calcitonin. Haemodialysis was initiated prior to surgery for hypercalcaemic crises. Postoperatively, she required calcium gluconate infusion for 2 weeks. CASE 2 A 53-year-old female had an incidental finding of hypercalcemia, which was subsequently confirmed to be PHPT. Serum calcium range was 2.92-3.02 mmol/L and phosphate 0.6-0.72 mmol/L. Serum iPTH 456.9 pg/ ml, 25-Hydroxy vitamin D 58.97 (25-75 nmol/L), ALP 372 U/L, and renal profile was normal. Parathyroid ultrasound showed a left extrathyroidal lesion measuring 0.6 x 0.7 x 0.8 cm, concordant with her sestamibi scan. DEXA scan showed osteoporosis. Preoperatively, she received IV bisphosphonate and cholecalciferol. She was discharged on day 3 with serum calcium of 2.05 mmol/L. However, she was re-admitted a day later for HBS (calcium 1.67 mmol/L) requiring calcium gluconate infusion for 3 days. RESULTS These cases illustrated severe HBS following parathyroidectomy. HBS may ensue in patients with elevated PTH and ALP, radiological evidence of bone diseases, large volume or weight of parathyroid gland, higher preoperative calcium, and vitamin D deficiency. CONCLUSION Rigorous proactive measures and timely management of HBS may avert the detrimental effects of hypocalcaemia. Identifying the likelihood that patients may develop HBS before surgery is of utmost importance for successful management.